2020
DOI: 10.1101/2020.04.14.039065
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimated regional white matter hyperintensity burden, resting state functional connectivity, and cognitive functions in older adults

Abstract: White matter hyperintensities (WMH) are linked to cognitive control; however, the structural and functional mechanisms are largely unknown. We investigated the relationship between WMH-associated disruptions of structural connectivity, resting state functional connectivity (RSFC), and cognitive control in older adults. Fifty-eight cognitively-healthy older adults completed cognitive control tasks, structural MRI, and resting state fMRI scans. We estimated inferred, WMH-related disruptions in structural connect… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 74 publications
(95 reference statements)
1
4
0
Order By: Relevance
“…For example, our finding that disconnection between the striatum and middle frontal gyrus appears early and increases progressively across older decades is consistent with the known role of these connections in age-associated decrements in memory and executive function ( Buckner, 2004 ). Similarly, the observed disconnection between the thalamus and middle frontal gyrus also becomes more severe in older decades and is consistent with previous studies linking disrupted frontal-striatal-thalamocortical pathways with the decline of cognitive control ( Jaywant et al, 2020 ). Disconnection of the precuneus to the cingulate gyrus (e.g., ventral posterior cingulate gyrus) is seen in the oldest decade.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For example, our finding that disconnection between the striatum and middle frontal gyrus appears early and increases progressively across older decades is consistent with the known role of these connections in age-associated decrements in memory and executive function ( Buckner, 2004 ). Similarly, the observed disconnection between the thalamus and middle frontal gyrus also becomes more severe in older decades and is consistent with previous studies linking disrupted frontal-striatal-thalamocortical pathways with the decline of cognitive control ( Jaywant et al, 2020 ). Disconnection of the precuneus to the cingulate gyrus (e.g., ventral posterior cingulate gyrus) is seen in the oldest decade.…”
Section: Discussionsupporting
confidence: 91%
“…One key mechanism by which WMH are thought to affect cognition is through the disconnection of associated gray matter regions ( Jaywant et al, 2020 ). Structural connectivity in the human brain can be inferred using diffusion tractography, and several studies have used diffusion tensor imaging (DTI) data to show that alterations in overall brain network connectivity are associated with cognitive deficits in cohorts of older subjects ( Tuladhar et al, 2016 ; Wiseman et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…88 Both structural and functional disconnection contribute unique variance to predicting cognitive functioning 89 and in cerebrovascular disease are associated with executive functioning. 90 The possibility that functional connectivity may shift or compensate for structural disconnection over time is also a relevant question to ensure that appropriate treatments are delivered depending on the time period post-stroke, especially as chronic stroke survivors can experience secondary degeneration in the thalamus, amygdala, hippocampus, and cingulum bundle. 91 A limitation of our review and of the literature is that is that it is often clinically and conceptually difficult to differentiate PSD from standalone apathy.…”
Section: Implications For Treating Post-stroke Depression With Executive Dysfunctionmentioning
confidence: 99%
“…As shown in Figures 3 and 5, cortico-subcortical connections involving the caudate, putamen, thalamus, and amygdala with regions of the frontal, parietal, and temporal lobes emerge as predictive of fluid cognition. The cortical regions implicated in fluid cognition comprise nodes of the frontoparietal network, dorsal attention network, cingulo-opercular task control network, and default mode network, all of which have been implicated in executive function (Reineberg et al, 2015, Spreng et al, 2010, Leech et al, 2011, Jaywant et al, 2020 and memory (Iidaka et al, 2006, Wallis et al, 2015, Dixon et al, 2017. The frontoparietal, dorsal attention, and cingulo-opercular networks are frequently implicated in maintaining and updating information in mind, shifting attention, inhibiting distractions, and facilitating goal-directed behaviour (Spreng et al, 2010, Iidaka et al, 2006, Wallis et al, 2015, Dixon et al, 2017.…”
Section: Cattell and Horn's Two-component Theory Of Intellectual Devementioning
confidence: 99%
“…In our results, we observe that many distributed cortical and subcortical regions are equally important when using SC to predict cognition, but only a few regions are important when using FC to predict cognition. Previous work (Jaywant et al, 2020) using a partial least squares regression approach to identify the relationship between inferred structural disconnection and cognitive inhibition observed that it was mostly structural connections that were important to predict cognition, with only two functional connections contributing additional unique variance. Our results here align with those findings; While functional and structural connections uniquely predict cognitive abilities, at a regional level there are more regions that are important for the prediction when using structural connectivity than when using functional connectivity.…”
Section: Cattell and Horn's Two-component Theory Of Intellectual Devementioning
confidence: 99%